On the James constant and B-convexity of Cesàro and Cesàro-Orlicz sequence spaces - Lech Maligranda (2018)
The classical James constant and the nth James constants, which are measure of B-convexity for the Cesàro sequence spaces cespand the Cesàro-Orlicz sequence spaces cesM, are calculated. These investigations show that cesp, cesMare not uniformly non-square and even they are not B-convex. Therefore the classical Cesàro sequence spaces cespare natural examples of reflexive spaces which are not B-convex. Moreover, the James constant for the two-dimensional Cesàro space ces2(2)is calculated. © 2006 Elsevier Inc. All rights reserved.